Comparative study of irrigation advance based infiltration methods for furrow irrigated soils - Shaikh, Irfan Ahmed; Wayayok, Aimrun; Mangrio, Munir Ahmed; Khatri, Kanya Lal; Soomro, Ashifa; Dahri, Saeed Ahmed (Universiti Putra Malaysia Press, 2017)
This study was attempted to evaluate infiltration methods based on irrigation advance for furrow irrigation. Irrigation advance data were collected at Latif farm, Sindh Agriculture University, Tandojam for three irrigation events. To achieve the objectives of the study two different methods viz. Upadhyaya and Raghuwanshi and Valiantzas one-point, were tested against the two-point method. Evaluation of employed methods was undertaken to know the best method for the prediction of cumulative infiltration and advance. The results revealed that Upadhyaya and Raghuwanshi (ME=-5.25) and Valiantzas one-point (ME=-0.99) are unsuitable for silt loam soil with their original constants as these methods show great scatter when compared with reference method and measured data. Thus, it is suggested that these methods must be evaluated before use.